Deep learning for internet of things infrastructure - Ghosh, Uttam; Alazab, Mamoun; Bashir, Ali Kashif; Pathan, Al-Sakib Khan (CRC Press, Taylor & Francis Group, 2022)
This book promotes and facilitates exchanges of research knowledge and findings across different disciplines on the design and investigation of deep learning (DL)–based data analytics of IoT (Internet of Things) infrastructures. Deep Learning for Internet of Things Infrastructure addresses emerging trends and issues on IoT systems and services across various application domains. The book investigates the challenges posed by the implementation of deep learning on IoT networking models and services. It provides fundamental theory, model, and methodology in interpreting, aggregating, processing, and analyzing data for intelligent DL-enabled IoT.